Continuous Neuromuscular Blockade for Bronchopulmonary Dysplasia - Johnson, Emily D.; Keppel, Kristopher; McNamara, LeAnn; Collaco, Joseph M.; Boss, Renee D. (American Journal of Perinatology, 2024)
Objective Bronchopulmonary dysplasia (BPD) is the most common late morbidity for premature infants. Continuous neuromuscular blockade (CNMB) is suggested for the most unstable phase of BPD, despite no outcome data. We explored the association between duration of CNMB for severe BPD and mortality.Design Medical record review of children <5 years old admitted from 2016 to 2022 with BPD and one or more course of CNMB for ≥14 days.Results Twelve children received a total of 20 episodes of CNMB for ≥14 days (range 14–173 d) during their hospitalization. Most (10/12) were born at <28 weeks' gestation and most (11/12) with birth weight <1,000 g; 7/12 were of Black race/ethnicity. All were hospitalized since birth. Most (10/12) were initially transferred from an outside neonatal intensive care unit (ICU), typically after a >60-day hospitalization (9/12). Half (6/12) of them had a ≥60-day stay in our neonatal ICU before transferring to our pediatric ICU for, generally, ≥90 days (8/12). The primary study outcome was survival to discharge: 2/12 survived. Both had shorter courses of CNMB (19 and 25 d); only one child who died had a course ≤25 days. Just two infants had increasing length Z-scores during hospitalization; only one infant had a final length Z-score > − 2.Conclusion In this case series of infants with severe BPD, there were no survivors among those receiving ≥25 days of CNMB. Linear growth, an essential growth parameter for infants with BPD, decreased in most patients. These data do not support the use of ≥25 days of CNMB to prevent mortality in infants with severe BPD.Key Points
Keywords: bronchopulmonary dysplasia; paralytic; pediatric; mortality